2021
DOI: 10.29259/ja.v15i1.11849
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kinerja Lingkungan Terhadap Carbon Emission Disclosure Dengan Dewan Komisaris Independen Sebagai Variabel Moderasi

Abstract: This study aims to test the effect of environmental performance on carbon emission disclosure with independent board of commissioners as moderation variables. Environmental performance measurement uses PROPER rating, carbon emission disclosure using Carbon Disclosure Project (CDP), while independent board of commissioners is measured by proportion of independent board of commissioners. The population in this study was a company that belonged to the non-financial sector in 2016-2018. Sample selection using purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
6

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 4 publications
3
11
0
6
Order By: Relevance
“…By disclosing the carbon emission disclosure, this indicates that they play an active role in reducing the greenhouse gas effect, tackling climate change, and creating a green economy. The result of this research is in line with the previous research conducted by Maulidiavitasari & Yanthi (2021), Nurlis (2019), and Saptiwi (2019) stated that environmental performance positively affects carbon emission disclosure.…”
Section: The Effect Of Environmental Performance On Carbon Emission D...supporting
confidence: 91%
See 1 more Smart Citation
“…By disclosing the carbon emission disclosure, this indicates that they play an active role in reducing the greenhouse gas effect, tackling climate change, and creating a green economy. The result of this research is in line with the previous research conducted by Maulidiavitasari & Yanthi (2021), Nurlis (2019), and Saptiwi (2019) stated that environmental performance positively affects carbon emission disclosure.…”
Section: The Effect Of Environmental Performance On Carbon Emission D...supporting
confidence: 91%
“…Therefore, when the company's environmental performance is high, the company's image will be higher because this indicates that the company cares about the environment in which the company operates. The results of previous studies conducted by Maulidiavitasari & Yanthi (2021), Nurlis (2019), andSaptiwi (2019) concluded that environmental performance proxied by PROPER had a positive effect on carbon emission disclosure. The positive relationship between environmental performance and carbon emission disclosure is because the high PROPER rating indicates that companies have been able to overcome the environmental matters so that the trust from external parties can be preserved (Nurlis, 2019).…”
Section: The Effect Of Environmental Performance On Carbon Emission D...mentioning
confidence: 87%
“…The Effect of Environmental Performance on the Disclosure of Carbon Emissions Maulidiavitasari and Yanthi (2021) suggest that companies that are active in environmental disclosure tend to be able to create a good environment and be able to formulate strategies in overcoming environmental problems. With the company's activeness in dealing with environmental problems, it can encourage companies to voluntarily disclose their environmental activities, including disclosure of carbon emissions.…”
Section: Environmental Profitabilitymentioning
confidence: 99%
“…It resulted in the function of the independent commissioner as a less effective supervisor to monitor management performance. In addition, the independent commissioner is a party that is not part of the company's internal, so it is not always in the company to oversee management performance for the benefit of shareholders (Maulidiavitasari & Yanthi, 2021).…”
Section: The Moderating Role Of the Independent Commissioner In The A...mentioning
confidence: 99%